Psychophysiological factors are not directly associated to heart rate variability in athletes: A meta-analysis - Lapo, H. M.; Chacon-Mikahil, M. P. T.; Sardeli, A. V. (Journal of Mental Health & Clinical Psychology, 2024)
Objective: Although heart rate variability (HRV) has been a useful and accessible tool to monitor recovery from athletes` training, it is not clear if it reflects changes in psychophysiological factors. The aim of these study is to identify, through a systematic review and meta-analyses, whether the psychophysiological factors are associated with alteration in heart rate variability (HRV) in sports.